2002
DOI: 10.1029/2001jb001607
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetism of Upper Vendian sediments from the Winter Coast, White Sea region, Russia: Implications for the paleogeography of Baltica during Neoproterozoic times

Abstract: [1] Paleomagnetic results from an Upper Vendian sedimentary sequence exposed along the White Sea shoreline, NW Russia are described. These classical exposures have been the subject of intense paleontological investigations due to their well-preserved Ediacara fauna, but no paleomagnetic results have as yet been published. A total of 337 hand samples and 210 oriented drill cores (35 sites) along three profiles have been collected at the locality (65.5°, 40.0°E) where a 555 ± 3 Ma U-Pb age of comagmatic zircons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 25 publications
1
30
1
1
Order By: Relevance
“…10, solid arrow). This is not the case if we include the latest paleomagnetic studies for Vendian lithologies in Baltica (e.g., Eneroth et al 2004;Llanos et al 2005;Popov et al 2002), which place Baltica closer to the equator (Fig. 10, dashed arrow).…”
Section: Paleomagnetic Poles and Age Determinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…10, solid arrow). This is not the case if we include the latest paleomagnetic studies for Vendian lithologies in Baltica (e.g., Eneroth et al 2004;Llanos et al 2005;Popov et al 2002), which place Baltica closer to the equator (Fig. 10, dashed arrow).…”
Section: Paleomagnetic Poles and Age Determinationsmentioning
confidence: 99%
“…When comparing the Jänisjärvi pole to the data set for Baltica (e.g., Meert et al 2003;Torsvik et al 1996;Torsvik et al 2001), we notice that it plots on the Cambrian part of the APWP segment, close to the 500 Myr pole derived from Andrarum limestone. Recently, the reliability of the existing data between 750 and 500 Myr has been questioned (e.g., Eneroth et al 2004;Llanos et al 2005;Popov et al 2002), mainly because the data are sparse and of ambiguous interpretation. Torsvik et al (1996) place Baltica at very high latitudes in the southern hemisphere during the period spanning 616 to 500 Myr (Fig.…”
Section: Paleomagnetic Poles and Age Determinationsmentioning
confidence: 99%
“…The low-latitude model was favored because it allowed for a close relationship between Siberia and the arctic margin of Laurentia until ~550 Ma (see also Pelechaty, 1996). New data from Baltica (Popov et al, 2002) However, paleomagnetic data from early and late Cambrian sediments from northern Norway and Sweden Rehnström, 2001 and indicate relatively slow motion from 580 Ma to 500 Ma. Furthermore, a recent re- …”
Section: -560 Ma Reconstructions (Vendian Glaciations)mentioning
confidence: 99%
“…A Neoproterozoic (750 Ma) mean pole has been calculated by Torsvik et al (1996) and with decreasing age this is followed by the Egersund pole (616 Ma;Poorter, 1972;Storetvedt, 1966;Bingen et al, 1998), the A-and B-poles of Ukrainian trap magmatism (ca. 580, 580-561, and 582-545 Ma, respectively;Elming et al, 2007;Nawrocki et al, 2004), the Fen pole (583 Ma; Piper, 1981;Meert et al, 1998), the Z-pole of the Winter Coast (555 Ma; Popov et al, 2002), the Zolotica 2 and Stappogiedde poles (550 Ma; Llanos et al, 2005), the pole of the Dividal Group (535 Ma; Rehnström and Torsvik, 2003), and the pole of the Andarum limestone (ca. 500 Ma; Torsvik and Rehnström, 2001).…”
Section: Paleomagnetic Constraintsmentioning
confidence: 99%
“…555 Ma Z-pole, and Zolotica and Stappogiedde poles are similar to a pole that Elming et al (C-pole; interpreted as secondary, of Late Ediacaran or Devonian age. Popov et al (2002) and Llanos et al (2005) suggested an apparent polar wander path for Baltica with a different selection of poles, and polarities of the 550-555 Ma poles opposite to poles of similar age, as presented in Elming et al (2007). Here for Baltica the A-poles of the Ukrainian traps, which are located on the northern hemisphere not far from the Egersund pole, are chosen to represent a magnetization of ca.…”
Section: Paleomagnetic Constraintsmentioning
confidence: 99%